Using South Africa s woodlands wisely - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
In South Africa a valuable forest-based economy has emerged, based on new and traditional areas of resource use, including medicines, foods and handicrafts. The trade in natural forest and woodland products involves a growing number of people, much of it